Sterol-dependent membrane association of the marine sponge-derived bicyclic peptide Theonellamide A as examined by 1H NMR. Issue 21 (1st November 2016) - Cornelio, Kimberly; Espiritu, Rafael Atillo; Todokoro, Yasuto; Hanashima, Shinya; Kinoshita, Masanao; Matsumori, Nobuaki; Murata, Michio; Nishimura, Shinichi; Kakeya, Hideaki; Yoshida, Minoru; Matsunaga, Shigeki
Graphical abstract: Abstract: Theonellamide A (TNM-A) is an antifungal bicyclic dodecapeptide isolated from a marine sponge Theonella sp. Previous studies have shown that TNM-A preferentially binds to 3β-hydroxysterol-containing membranes and disrupts membrane integrity. In this study, several 1 H NMR-based experiments were performed to investigate the interaction mode of TNM-A with model membranes. First, the aggregation propensities of TNM-A were examined using diffusion ordered spectroscopy; the results indicate that TNM-A tends to form oligomeric aggregates of 2–9 molecules (depending on peptide concentration) in an aqueous environment, and this aggregation potentially influences the membrane-disrupting activity of the peptide. Subsequently, we measured the 1 H NMR spectra of TNM-A with sodium dodecyl sulfate- d 25 (SDS- d 25 ) micelles and small dimyristoylphosphatidylcholine (DMPC)- d 54 /dihexanoylphosphatidylcholine (DHPC)- d 22 bicelles in the presence of a paramagnetic quencher Mn 2+ . These spectra indicate that TNM-A poorly binds to these membrane mimics without sterol and mostly remains in the aqueous media. In contrast, broader 1 H signals of TNM-A were observed in 10 mol % cholesterol-containing bicelles, indicating that the peptide efficiently binds to sterol-containing bilayers. The addition of Mn 2+ to these bicelles also led to a decrease in the relative intensity and further line-broadening of TNM-A signals, indicating that the peptide stays near the surface of the bilayers. A comparison of the relative signal intensities with those of phospholipids showed that TNM-A resides in the lipid–water interface (close to the C2′ portion of the phospholipid acyl chain). This shallow penetration of TNM-A to lipid bilayers induces an uneven membrane curvature and eventually disrupts membrane integrity. These results shed light on the atomistic mechanism accounting for the membrane-disrupting activity of TNM-A and the important role of cholesterol in its mechanism of action.